Spinal epidural lipomatosis due to obesity presenting with back and leg pain and weakness successfully treated with weight loss - Yasunori Nagahama, M.D.; Marshall T. Holland, M.D., M.S; Patrick W. Hitchon, M.D. (Interdisciplinary Neurosurgery, 2019)
Spinal Epidural Lipomatosis (SEL) is an uncommon but previously characterized ailment typified by excessive overgrowth epidural adipose tissue. This overgrowth may lead to compression of local tissue including the underlying thecal space and nervous tissues. Common causes are medication induced (particularly glucocorticoid administration) and obesity. Prompt recognition of the diagnosis and initiation of treatment, be it medication stoppage or surgical decompression is imperative. In this report we describe the case of a 51-year-old female who presented with back and leg pain. She was diagnosed with SEL due to obesity with noted compression of the underlying nervous tissue noted on MRI. The patient was successfully treated with a course of weight loss with remarkable clinical and noted resolution of thecal sac compression on follow up MRI. Early consideration of this entity can increase the likelihood of timely diagnosis and successful treatment. Keywords: Spinal epidural lipomatosis, Conservative management, Obesity, Glucocorticoids, Weight loss, Epidural adipose